201k views
5 votes
Factor the following problem thank you so much

Factor the following problem thank you so much-example-1

2 Answers

1 vote

Answer:

(3a-2)(3a+4)

Explanation:

9a^2+6a-8

9a^2+(12-6)a-8

9a^2+12a-6a-8

3a(3a+4)-2(3a+4)

(3a+4)(3a-2)...factors

Hope it Helps you!!

User Simon Xu
by
4.9k points
3 votes

Answer:

Explanation:

Sum = 6

Product = -72

Factors = 12 , (-6) {12 +(-6) = 6 & 12*(-6) = -72}

9a² + 6a - 8 = 9a² + 12a - 6a - 8

= 3a(3a + 4) - 2(3a + 4)

= (3a + 4)(3a - 2)

Hint: 9a² + 12a = 3a*a + 3a*4 = 3a(3a + 4)

-6a - 8 = -2 * 3a - 2 * 4 = -2(3a + 4)

User Gissel
by
5.1k points